Transformation of Abdominal Wall Endometriosis to Clear Cell Carcinoma - Maria Paula Ruiz; Darryl Lewis Wallace; Matthew Thomas Connell (Hindawi Limited, 2015)
Clear cell carcinoma is the least common of the malignant transformations reported in nonpelvic sites of endometriosis. Two cases with clear cell carcinoma transformation arising from endometriosis in abdominal wall scars are presented. These patients underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy, pelvic washings, and abdominal wall lesion resection. The first case had initial treatment with chemotherapy, while chemotherapy and radiation therapy were given for the second case. A recurrence was noted for the chemotherapy only case for, which she was subsequently given radiation, with further resolution of the lesion.